Kemampuan Calon Pendidik Dalam Memanfaatkan Teknologi Komputer Untuk Mengembangkan Multimedia Pembelajaran Matematika - Sulistyani, Niluh (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2016)
This study was aimed to describe ability of prospective student educators in using computer technology to develop mathematics learning multimedia. The ability was used to develop Power Point multimedia and Adobe Flash multimedia. This study was descriptive research with 27 prospective student educators as a subject. Researcher was main instrument assisted product evaluation rubric and questionnaire. The result showed that the average of ability of prospective student educators in using computer technology was in good category. The average score were 77,59Â  in using Power Point multimedia and 74,54 in using Adobe Flash multimedia. The ability was sufficiently to be used in learning and teaching. From the product analyzed and questionnaire, we found that the ability were not maximal because there were many tools untapped primarily in Adobe Flash. Unfamiliar yet in used also became a factor that affected the ability of prospective educators in using computer technology.Â Keywords: The ability in using computer technology, mathematics learning multimedia, prospective educators